Batalha das máscaras: animação experimental digital baseada nas cavalhadas de Pirenopólis - Teixeira, Iuri Araújo Cardoso (2015)
The main objective of this work was develop an experimental 2D animation which used digital resources to simulate traditional artistic techniques of drawing and painting. For this, I made a historical survey of experimental animation around the world, until the emergence of the first Brazilian productions. For references, animation analysis of five experimental artists and animators from countries like Brazil, Canada, United States, Russia and Japan. Based on these analyzes, there was the application of its artistic and cinematographic methods, exploring simulations of materials like oil pastel, colored pencil, acrylic paint and moving cameras via software. The narrative theme selected for the development of an animated story was the festival of Cavalhadas in Pirenópolis, representing its medieval origin in Europe, until his arrives in Brazil and the state of Goiás, showing its relevance as a regional cultural event.